(untitled) (Research, Society and Development, 2020)
Heart failure is characterized as the lack of blood pumping capacity performed by the heart, which is considered a public health problem worldwide. Due to HF, the individual can develop clinical aspects that impact cognitive function and, consequently, self-care. Therefore, this study aimed to investigate cognitive changes and self-care in patients affected by HF and compare it with the cognitive and self-care changes of healthy participants. This is a quantitative, epidemiological, cross-sectional case-control study carried out at an institution in the city of Belém, Pará, Brazil. The following tests were used for data collection: Montreal Cognitive Assessment, Digit Symbol Substitution Test, European Heart Failure Self-care Behavior Scale (EHFScBS). Data were tabulated in Microsoft Excel 2010 and statistically treated by Epi Info version 3.5.2 with a 5% significance level and considering a 95% confidence interval in all analyzes. It was observed that patients with HF have slightly better self-care compared to patients without HF with scores obtained by EHFScBS equal to 29.7 ± 6.9 and 31.8 ± 8.2, respectively. Additionally, patients with HF showed impairments in the three cognitive domains, and women with HF demonstrated greater cognitive impairment compared to the other participants. The present study provides data to help build new approaches to interventions by the multidisciplinary team to promote better self-care and avoid cognitive impairments in patients with HF.